Value Added Tax (VAT) in Nepal: A Critical Assessment of Its Performance - Koirala, Kamal (Journal of Nepalese Business Studies, 2012)
Value Added Tax (VAT) is a recent phenomenon in the arena of tax administration in Nepal. This paper aims to assess critically the performance of VAT in Nepal since its inception to date, focusing basically on three aspects of it, viz, (i) Current scenario of VAT administration (ii) Major issues, and (iii) Urgent corrective actions required. Most of the qualitative and quantitative relevant data have been collected from Economic Survey and office of Inland Revenue Department (IRD). The data comprises of both primary and secondary data. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 63-69 Uploaded date: July 8, 2012